N-Arylation of 3-Formylquinolin-2(1h)-Ones Using Copper(Ii)-Catalyzed Chan–Lam Coupling - Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
3-formyl-2-quinolones have attracted the scientific community’s attention because they are used as versatile building blocks in the synthesis of more complex compounds showing different and attractive biological activities. Using copper-catalyzed Chan–Lam coupling, we synthesized 32 new N-aryl-3-formyl-2-quinolone derivatives at 80 °C, in air and using inexpensive phenylboronic acids as arylating agents. 3-formyl-2-quinolones and substituted 3-formyl-2-quinolones can act as substrates, and among the products, the p-methyl derivative 9a was used as a substrate to obtain different derivatives such as alcohol, amine, nitrile, and chalcone. © 2022 by the authors.